3D hierarchical heterostructure assembled by NiFe LDH/(NiFe)Sx on biomass-derived hollow carbon microtubes as bifunctional electrocatalysts for overall water splitting. (10th July 2020) - Zou, Yajun; Xiao, Bing; Shi, Jian-Wen; Hao, Han; Ma, Dandan; Lv, Yixuan; Sun, Guotai; Li, Jun; Cheng, Yonghong
Abstract: Developing highly active and stable noble-metal-free bifunctional electrocatalysts for both hydrogen and oxygen evolution is still a challenge in electrochemical water splitting technology. Herein, a three-dimensional (3D)-networked heterogeneous electrocatalyst in the form of vertically aligned NiFe layered double hydroxide (LDH) nanoflakes coupled with Fe-doped NiSx nanoparticles is supported on biomass-derived carbon microtubes (CMT). The optimal hybrid electrode exhibits superior electrocatalytic activity with low overpotentials of 210 and 157 mV to deliver a current density of 10 mA cm −2 for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in 1 M KOH, respectively. It is revealed that the remarkable features of the catalyst lie in the unique 3D open configuration, the high conductivity of CMT support and the strong interfacial coupling effects between NiFe LDH and (NiFe)Sx, giving rise to enhanced active sites, accelerating electron/ion transport, and further promoting reaction kinetics of OER/HER. Furthermore, an alkaline water electrolyzer is constructed with the NiFe LDH/(NiFe)Sx /CMT composite as catalyst for both anode and cathode. This electrolyzer displays excellent electrolysis performance (affording 10 mA cm −2 at 1.53 V) and long-term durability over 100 h. This work demonstrates a strategy in preparing bifunctional and cost-efficient electrocatalysts with potential application in the future. Graphical abstract: Image 1 Highlights: NiFe LDH/(NiFe)Sx /CMT was fabricated for overall water splitting for the first time. In-situ growth strategy ensured the formation of an integrated electrocatalytic system. Strong interactions optimized the binding energies for OER and HER reactions. NiFe LDH/(NiFe)Sx /CMT exhibited superior electrocatalytic activity with low overpotentials.